Apoio pedagógico oferecido a crianças e adolescentes com câncer em um hospital pediátrico - Garrito, Giulia Isabelle Marinho [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Hospital Pedagogy is a teachingmodalitydesigned to assist and accompany the education of hospitalized children who, due to an illness, are unable to attend school and need to continue theirstudies. The initial idea of Hospital Pedagogy arose in 1935, when a school for maladaptive children was inaugurated in Suresnes, France, and since then, several countries have invested in the development of these hospital classes, although many still need to improve social and pedagogical ideals competent in that context. In Brazil, according to theStatute ofChildren andAdolescents(ECA), educationis a right of all children and young people and, considering the need to continue the school journey of hospitalized children, it was necessary to create new resolutions contained in the Statute of the Rights of the Hospitalized Child and Adolescent.Themain objective ofthis work isto analyze the proposalsfor pedagogicalsupport offered to children and adolescents with cancer in a Children's Center in a medium-sized city in the interior of São Paulo, in addition to observing how itsimplementation influencesthe treatment and general development of the child, by conception. of educators. This qualitative research was based on two data collection instruments: document analysis and semi-structured interview.The latter is carried out with teachers who teach the classes offered by the center, taking into account the context of pediatric care in which they are inserted,andhighlightingtheimportanceofthisspecialized support andhowitinterferesintheeducational development of different ages. At the end of data collection, the data were organized and according to the content analysis proposed by BARDIN (2009). It should be noted that the hospital class is extremely important and necessary not only for the educational development of hospitalized children, but also to bring to light the need for games and interactions essential to childhood and child development.However, even though it is a very important teachingmodality regulated by the implementation of legislation, there is a need for professional training with regard to the curriculum of Pedagogy and Licentiate courses in Brazil.

A Pedagogia Hospitalar é uma modalidade de ensino desenvolvida para auxiliar e acompanhar a educação de crianças hospitalizadas que, por motivo de alguma doença não conseguem frequentar a escola e precisam dar continuidade aos estudos. A ideia inicial da Pedagogia Hospitalar surgiu em 1935, quando foi inaugurada uma escola para crianças inadaptadas em Suresnes, na França, e, desde então, diversos países têm investido no desenvolvimento dessas classes hospitalares, ainda que muitos ainda precisem aperfeiçoar os ideais sociais e pedagógicos envolvidos nesse contexto. No Brasil, de acordo com o Estatuto da Criança e do Adolescente (ECA), a educação é um direito de todas as crianças e jovens e, considerando a necessidade de continuidade da jornada escolar de crianças hospitalizadas, fez-se necessário a criação de novas resoluções contidas no Estatuto dos Direitos da Criança e do Adolescente Hospitalizado. Este trabalho tem por objetivo principal analisar as propostas de apoio pedagógico oferecidos a crianças e adolescentes com câncer de um Centro Infantil em uma cidade de médio porte do interior paulista, além de observar como sua execução influencia no tratamento e desenvolvimento geral da criança, pela concepção dos educadores. Trata-se de pesquisa qualitativa a qual teve como base dois instrumentos de coleta de dados: análise documental e entrevista semiestruturada. Esta última realizada com dois professores que ministram as aulas oferecidas pelo referido centro, levando em consideração o contexto de atendimento pediátrico em que estão inseridas, e evidenciando a importância desse apoio especializado e como ele interfere no desenvolvimento educacional de diferentes idades. Ao final da coleta de dados, os dados foramorganizados e analisados segundo a análise de conteúdo proposto por BARDIN (2009). Nota- se que a classe hospitalar é extremamente importante e necessária não só para o desenvolvimento educacional das crianças hospitalizadas, mas também para trazer à tona a necessidade de brincadeiras e interações essenciais à infância e ao desenvolvimento infantil. Porém, ainda que seja uma modalidade de ensino muito importante regularizada pela implantação de uma legislação, nota-se a necessidade de capacitação profissional no que diz respeito ao currículo dos cursos de Pedagogia e Licenciatura no Brasil.
Pedagogical support offered to children and adolescents with cancer in a pediatric hospital
Keywords: Hospital pedagogy; Specialized service; Pedagogical proposals; Education and phsychological development; Pedagogia hospitalar; Atendimento especializado; Propostas pedagógicas; Desenvolvimento educacional e pedagógico; Câncer